2023
DOI: 10.7759/cureus.42926
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Obesity on Cognitive Functioning Among Healthcare Professionals: A Comprehensive Analysis

Abstract: BackgroundExcessive body fat, or obesity, is a worldwide epidemic and a major contributor to the development of dementia. AimThe research aimed to determine how obesity affected healthcare professionals' memory performance. Materials and MethodA total of 474 participants (both male and female) were recruited in this study by random sampling method from three different health institutions. Participants were categorized into overweight, normal weight, and obese groups based on their body mass index (BMI) as per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Significant differences were observed in the level of general frequency of forgetting, the seriousness of forgetting, retrospective functioning, and mnemonics usage in relation to different body mass indexes and body fat percentage classes (p < 0.05). The findings showed a positive correlation between excessive body fat and general frequency of forgetting and seriousness of forgetting, whereas a negative correlation was observed to retrospective functioning and mnemonics usage [77]. In terms of memory subdomains, many studies found obese persons to suffer from working memory deficits [75,78,79].…”
Section: Cognitive Ability Domainsmentioning
confidence: 98%
“…Significant differences were observed in the level of general frequency of forgetting, the seriousness of forgetting, retrospective functioning, and mnemonics usage in relation to different body mass indexes and body fat percentage classes (p < 0.05). The findings showed a positive correlation between excessive body fat and general frequency of forgetting and seriousness of forgetting, whereas a negative correlation was observed to retrospective functioning and mnemonics usage [77]. In terms of memory subdomains, many studies found obese persons to suffer from working memory deficits [75,78,79].…”
Section: Cognitive Ability Domainsmentioning
confidence: 98%
“…HE CONDITION of obesity is a significant worldwide health issue that has wide-ranging implications, including its notable influence on cognitive abilities. An increasing amount of scholarly research has shed light on a strong correlation between obesity and cognitive impairment, which includes deficiencies in memory, attention, executive functions, and overall cognitive abilities (1). The association between these factors is of particular concern due to the escalating global prevalence of obesity.…”
mentioning
confidence: 99%